2006
DOI: 10.1063/1.2338136
|View full text |Cite
|
Sign up to set email alerts
|

Influence of A-site disorder on the half-doped manganites

Abstract: The electronic transport and magnetism in half-doped Nd0.50Ca0.25Sr0.25MnO3 manganites have been investigated. Contrary to general half-doped system, it only displays a paramagnetic-ferromagnetic phase transition associated with an insulator-metal transition instead of with any features of charge ordering. With the decrease of temperature, an electronic phase separation and spin glass state occur in low temperature. We suggest that the A-site cation disorder induced by the size mismatch between Sr2+ ion and Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 39 publications
1
3
0
Order By: Relevance
“…It should be noted that for all doped samples, an inflexion in ρ-T curves is observed at the semiconductorlike region, which is a characteristic for the existence of the CO phase [19]. This property is consistent with that reported in the Nd 0.5 Ca 0.5 MnO 3 system [18,20]. The temperature corresponding to the inflexion in the ρ-T curves is defined as T CO .…”
supporting
confidence: 86%
“…It should be noted that for all doped samples, an inflexion in ρ-T curves is observed at the semiconductorlike region, which is a characteristic for the existence of the CO phase [19]. This property is consistent with that reported in the Nd 0.5 Ca 0.5 MnO 3 system [18,20]. The temperature corresponding to the inflexion in the ρ-T curves is defined as T CO .…”
supporting
confidence: 86%
“…However, in the present materials, these characters have not been observed. In our previous investigation [14], we have suggested that the A-site cation disorder induced by the size mismatch between Sr 2 + ion and Ca 2 + ion was mainly responsible for this phenomenon. However, for further understanding the above behavior, two important questions about PM-FM transition should be firstly considered: one is the order of phase transition, the other is the common universality class.…”
Section: Methodsmentioning
confidence: 97%
“…The detailed experimental process has been reported in Ref. [14]. The Powder X-ray diffraction was employed on Japan Rigaku D/max-ga rotating powder diffractometer using Cu Ka radiation to check the structure and phase purity.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation